Oil extracts from fresh and dried Iban ginger - Nurul Mirzha Syerliza, Halimin; Mohammad Omar, Abdullah; Noraziah, Abdul Wahab; Radzuan, Junin; Awang Ahmad Sallehin, Awang Husaini; Augustine, Agi (Elsevier Science, Ltd., 2022)
The present study aims to investigate the chemical properties of a new ginger species called Iban ginger. Oil extracts yield from both fresh and dried Iban ginger were compared via Soxhlet extraction production method. Subsequently, the chemical composition of the extracts was characterized and analysed. The associated chemical constituents and bioactive compounds were explored using gas chromatograph mass spectrometry (GCMS) and Fourier transformed infrared spectroscopy (FTIR) analysis for chemical constituents and plant active compound study. Results obtained show that yield of the oil increases with the increase of extraction time, freshness of ginger and type of solvent use. Although Iban ginger is known to be comparatively hotter in taste, the bioactive compounds properties are similar or in close agreement with other types of gingers reported in literature. Finally, acetone equivalent-extraction time of recycled ethanol is introduced herewith and found to be minimum around 2 h, as far as the present study is concerned